Active Fuelling of a Passenger Car Sized Pre-Chamber Ignition System with Gaseous Components of Gasoline - Russwurm, Tim; Schumacher, Moritz; Wensing, Michael (SAE Technical Papers, 2020)
Homogeneous lean or diluted combustion can significantly increase the efficiency of spark ignition engines. Active fuelled pre-chamber ignition systems can overcome the problem that common spark ignitions systems are incapable to ignite strongly diluted mixtures. A small portion of the charge is burned in a separated chamber, which is connected to the main chamber by multiple small orifices. The combustion inside the pre-chamber generates hot gases, which penetrate into the main chamber and ignite the diluted charge on multiple sites. Active pre-chamber ignition systems feature a separate fuelling or scavenging system in addition to the one of the main combustion chambers. Preferably, gaseous fuel is used for the pre-chamber fuelling allowing better dosing accuracy and mixture preparation inside the pre-chamber. Using the mixture of air and gasoline vapour present in the fuel tank above the liquid level for fuelling the pre-chamber is one key element enabling an active pre-chamber ignition system for passenger cars. An experimental setup was built to simulate a fuel tank under different environmental conditions. The composition of the gasoline vapour-Air-mixture inside the tank was analyzed for various industry known reference fuels under extreme conditions. The necessary concentration of hydrocarbons was accomplished with all tested fuels. Additionally, the system was integrated into a engine testbench to analyze the engine combustion depending on the pre-chamber fuelling. The dosing of gasoline vapour-Air-mixture into the pre-chamber is implemented via a solenoid valve together with a self-developed check valve. Investigations in the especially critical low-load range show stable engine combustion in all conditions if the dosed mass of the fuel vapor-Air-mixture is adapted to the concentration of hydrocarbons present in this mixture.
Created from Fastlane, Scopus look-up

A Gasoline Fuelled Pre-Chamber Ignition System for Homogeneous Lean Combustion Processes - Schumacher, Moritz; Wensing, Michael (SAE Technical Papers, 2016)
Pre-chamber ignition systems enable the combustion of homogeneous lean mixtures in internal combustion engines with significantly increased thermal efficiency. Such ignition systems provide a much higher ignition energy compared to a common spark ignition by burning a small portion of the charge in a separate chamber, generating multiple ignition sites in the main combustion chamber and increasing the turbulent flame speed. Pre-chamber ignition systems are commonly used in large natural gas engines but the integration in automotive engines is not feasible so far due to the lack of suitable fuelling systems needed to keep the pre-chamber mixture stoichiometric at lean operation of the engine. Based on preliminary investigations we developed an ignition system with fuelled pre-chamber for automotive engines utilizing the available space for the conventional spark plug. These investigations proved the thermal stability and function of the system up to a specific power of 100 kW/l and a speed of 12500 rpm. The fuelling system saturates air with fuel vapour and injects this mixture time-controlled into the pre-chamber. The already available fuel tank ventilation system in Otto-engine powered cars can provide such an air-gasoline-vapour mixture. Further, the system uses an inexpensive low pressure solenoid valve to control the pre-chamber enrichment. The prototype of the pre-chamber incorporates a spark plug, fuelling valve, thermocouple and pressure transducer and was measured in a full engine at characteristic operating points regarding thermal efficiency, combustion process and emissions. The ignition system showed the ability to ignite highly diluted mixtures with = 1.6 and an efficiency gain of 14.8% compared to stoichiometric spark plug operation at 4.5 bar IMEP and 1500 rpm with a NOx emission below 100 ppm.
Created from Fastlane, Scopus look-up

Combustion process development for a SI engine with low pressure hydrogen direct injection - Schumacher, Moritz; Wensing, Michael (7th World Hydrogen Technologies Convention, 2017)

Combustion Process Development for Low Pressure Hydrogen Direct Injection - Schumacher, Moritz; Wensing, Michael (12. Tagung Gasfahrzeuge. 24-25 Oktober 2017, Stuttgart, 2017)
Keywords: Wasserstoffmotor; Direkteinblasung; LOHC

Einfluss des Brennverfahrens auf die Thermodynamik des Wasserstoffmotors mit Niederdruck-Direkteinblasung - Schumacher, Moritz (Friedrich-Alexander-Universität Erlangen-Nürnberg, 2019)
Die Entwicklung von Wasserstoffmotoren hat vor allem seit den 2000er Jahren eine Vielfalt von Brennverfahren hervorgebracht. Bei reinen Forschungsprojekten zeigen dabei Konzepte mit Hochdruck-Direkteinblasung, global magerer Schichtladung und hoher Verdichtung das größte Potential hinsichtlich des Wirkungsgrades und der Abgasemissionen. Eine Analyse möglicher Wasserstoff-Speichertechnologien und deren Randbedingungen ergibt allerdings, dass unabhängig von der Art der Wasserstoffspeicherung in praktischen Anwendungen ein kontinuierlicher Versorgungsdruck von maximal 20 bar zu erwarten ist. Da eine zusätzliche Verdichtung des Wasserstoffs aufgrund dessen geringer Dichte mit großen Wirkungsgradverlusten verbunden ist, kann für reale Anwendungen ausschließlich ein Brennverfahren mit Niederdruck-Direkteinblasung in Frage kommen. Betrachtet man die publizierten Arbeiten in diesem Bereich, so fällt auf, dass deren Anzahl und Umfang deutlich geringer ist, weshalb viele Fragen zu Brennverfahren mit Wasserstoff-Niederdruck-Direkteinblasung weiterhin offen sind. Die vorliegende Arbeit untersucht daher die Einflussparameter des Brennverfahrens auf die Thermodynamik von Wasserstoffmotoren mit Niederdruck-Direkteinblasung und gibt Empfehlungen für die optimale Gestaltung eines solchen Brennverfahrens. Hierfür wird ein moderner PKW-Motor auf den Betrieb mit Wasserstoff umgerüstet und experimentell untersucht. Dies umfasst die Entwicklung eines geeigneten Injektors und dessen umfangreiche Qualifizierung für den Einsatz im Motor. Die Messungen werden, unterstützt durch eine simultan durchgeführte 1D-Motorsimulation, hinsichtlich des Wirkungsgrades, der Emissionen und des Brennverlaufs analysiert. Die Prozessverluste werden mittels Energiebilanzen und Verlustteilung bewertet. <br
Keywords: Wasserstoffmotor; Direkteinblasung; Verlustteilung; Brennverfahren; HPDI; LPDI

Experimental Study on an Engine with Low Pressure Hydrogen Direct Injection - Schumacher, Moritz; Wensing, Michael (6th World Hydrogen Technologies Convention, 2015)

Investigations on a new engine concept for small hydrogen power generation units using LOHCs - Schumacher, Moritz; Mederer, Thomas; Wensing, Michael (SAE Technical Papers, 2013)
New energy scenarios for decentralised stationary energy supply based on Liquid Organic Hydrogen Carriers (LOHC) offer an attractive application for hydrogen engines and are a reason why hydrogen engines become topical again. Since hydrogen stored in LOHCs is released under ambient pressure and temperatures of over 200°C, compression and cooling of the hydrogen is needed, lowering the system's overall efficiency. Direct injection of hydrogen is advantageous due to its low volumetric energy density and the tendency towards pre-ignition. The development objective is an injection and combustion strategy for an engine in the performance category below 15 kW and the described fuel supply scenario. Therefore, an one dimensional simulation model of the engine and the hydrogen supplying compressor was built. The simulation results show a large influence of the injection pressure on engine efficiency due to the hydrogen supplying compressor. For the studies presented here an engine with an extended expansion was built for an increased utilisation of exhaust gas enthalpy. The extended expansion was also implemented in the one dimensional simulation model. First results show enhanced indicated efficiency under high load conditions. Furthermore, preliminary investigations on hydrogen combustion have been carried out using an optically accessible hydrogen engine. Laser-induced fluorescence was applied to investigate the effect of varied injection pressures and timings on the processes of injection, mixture formation and combustion. The end-of-injection timing variation showed that approx. 90 °CA are necessary to generate a homogeneous mixture in the combustion chamber which limits the injection timing for homogeneous combustion concepts. Copyright © 2013 SAE International and Copyright © 2013 KSAE.
Created from Fastlane, Scopus look-up

Investigations on an Injector for a Low Pressure Hydrogen Direct Injection - Schumacher, Moritz; Wensing, Michael (SAE Technical Papers, 2014)
Hydrogen engines represent an economic alternative to fuel cells for future energy scenarios based on Liquid Organic Hydrogen Carriers (LOHC). This scenario incorporates LOHCs to store hydrogen from fluctuating renewable energy sources and deliver it to decentralised power generation units. Hydrogen engines were deeply investigated in the past decade and the results show efficiencies similar to CI engines. Due to the low energy density and tendency towards pre-ignition of hydrogen, the key element to reach high efficiency and a safe operation is a direct injection of the hydrogen. Because high injection pressure is not available in practical applications or would reduce the possible driving range, a low injection pressure is favourable. The low density leads to large flow cross sections inside the injector, similar to CNG direct injectors. So far, some research CNG and hydrogen low pressure direct injectors were investigated, but no commercial injector is available. The objective of this work is the development of a low pressure hydrogen direct injector, with the ability to run unlubricated in neat hydrogen and meeting the necessary flow rate for a stationary engine generating 7.5 kW per cylinder at 1500 rpm. To characterize the injector an injector test stand with coriolis mass flow meter and a needle lift measurement through laser triangulation was used. Supported by the results of the test stand an injector was build, meeting the mentioned requirements. The final design is based on a commercial available injector with modifications on the injector controller, the needle actuation and special surface treatments. The injector was bench tested under dry conditions for over 100 million cycles without failure or critical wear marks. The required mass flow rate was achieved at a relatively low pressure of 850 kPa, compared to prior publications. This low injection pressure is especially advantageous for engines running on LOHC based hydrogen, which is released at near ambient pressure and must be compressed before injection, reducing the systems overall efficiency. The presented injector will be used in a small hydrogen heat and power generation unit, which is part of a LOHC energy storage demonstrator project currently investigated by the BavarianHydrogen Center, a joint project of five Bavarian universities.
Created from Fastlane, Scopus look-up

Pre-Chamber Ignition System for Diluted Combustion Processes with Active Fuelling by Volatile Fuel Components - Russwurm, Tim; Schumacher, Moritz; Wensing, Michael (Workshop ENCOM 2019, Waischenfeld, 16./17.10.2019, 2019)

Pre-chamber Ignition System for Homogeneous Lean Combustion Processes with Active Fuelling by Volatile Fuel Components - Schumacher, Moritz; Russwurm, Tim; Wensing, Michael (Ignition Systems for Gasoline Engines, 2018)

Pre-Chamber ignition system with active fuelling: an enabler for homogeneous lean and diluted combustion processes - Russwurm, Tim; Schumacher, Moritz; Wensing, Michael (14th International AVL Symposium on Propulsion Diagnostics, 2020)